2009
DOI: 10.1007/s10661-009-1161-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fixed-fraction subsampling on macroinvertebrate bioassessment of rivers

Abstract: We investigated the effect of different subsample fractions on the variability of benthic invertebrate metrics. The results of six fractions 1/12, 1/6, 1/4, 1/3, 5/12 and 1/2 were compared to the results of the whole samples. Over 120 metrics were tested using five datasets: ecoregion Alps and four river types. In general, variability of metrics decreased with increasing subsample size, but variability varied greatly with the selected metric group and river type. Independent of river type, the highest variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
(59 reference statements)
0
13
1
Order By: Relevance
“…Cao et al (2002) showed that 500 individuals maximized the discriminatory power of similarity indices, while Ligeiro et al (2013a) reported that samples with <300 individuals processed had less precision than those with 300 individuals. However, the accuracy and precision of the processing may also depend on the stream type, the metric being used (e.g., species richness versus a functional metric or a multimetric index; Petkovska and Urbanič 2010;Marzin et al 2012), and the level of taxonomic identification (Whittier and Van Sickle 2010).…”
Section: Subsampling and Sorting Proceduresmentioning
confidence: 99%
“…Cao et al (2002) showed that 500 individuals maximized the discriminatory power of similarity indices, while Ligeiro et al (2013a) reported that samples with <300 individuals processed had less precision than those with 300 individuals. However, the accuracy and precision of the processing may also depend on the stream type, the metric being used (e.g., species richness versus a functional metric or a multimetric index; Petkovska and Urbanič 2010;Marzin et al 2012), and the level of taxonomic identification (Whittier and Van Sickle 2010).…”
Section: Subsampling and Sorting Proceduresmentioning
confidence: 99%
“…Microhabitat types were defined as a combination of substrate and flow type with coverage of at least 5%. Samples then underwent laboratory sub-sampling procedures, and benthic organisms from a quarter of the whole field sample were identified and enumerated (Petkovska & Urbanič, 2009). Benthic invertebrates were determined to the taxonomic level used for the assessment of ecological river status in Slovenia (OGRS, 2009), i.e.…”
Section: Datamentioning
confidence: 99%
“…The continued sensitivity of this index when a six-quadrat assemblage was used for the comparative analysis among the reference, moderately impaired, and severely impaired sites indicates that this subsample size is useful in practical applications. Petkovska and Urbanic (2009) studied the effect of fixed-fraction subsampling on the variability of metrics, and found that, for most types of metrics and streams, the main decrease in variability occurs up to a subsample size of 1/4 of the original. This subsample size could therefore become widely applied.…”
Section: Discussionmentioning
confidence: 99%
“…Any instability of the metrics can directly impact the practical result of the assessment and, consequently, the management and preservation of the ecosystem (Lenat and Barbour 1994;Petkovska and Urbanic 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation